(untitled) - Liebaert, Richard M. (Menlo Park, California, 1997)
This section, which is the heart of the study guide, contains activities such as question, diagrams, crossword puzzles, problems, and fill-in-the-blank stories that will help you master the concepts in the text. Some exercises in this section relate to single modules, others connect the information and concepts of several modules.
Keywords: Biology,Life sciences,Natural history